2017
DOI: 10.1007/s10329-017-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

Proximity and grooming patterns reveal opposite-sex bonding in Rwenzori Angolan colobus monkeys (Colobus angolensis ruwenzorii)

Abstract: Close proximity and social grooming are important bonding mechanisms in primates. These behaviors show the social structure of a species and many studies have found positive correlations between the degree of kinship and grooming and proximity. We used 1 year of data collected via instantaneous scan sampling on a large "supertroop" of Colobus angolensis ruwenzorii at Lake Nabugabo, Uganda, to examine partner preferences for grooming and nearest neighbors in each age-sex class. Little is known about this specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…This aligns with what is known about their dispersal patterns, as males tend to disperse from their natal band prior to sexual maturity, limiting the opportunities for this sex to form long-term bonds with other core unit members 6668 (although see 6869 ). Previous work on our study population found that cross-sex bonding is stronger than bonding among the sexes 52 , a pattern associated with bi-sexual dispersal in other primates 80 . Bi-sexual dispersal is supported in this subspecies, as over the course of the year, we observed a total of eight dispersals, four females and four males.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This aligns with what is known about their dispersal patterns, as males tend to disperse from their natal band prior to sexual maturity, limiting the opportunities for this sex to form long-term bonds with other core unit members 6668 (although see 6869 ). Previous work on our study population found that cross-sex bonding is stronger than bonding among the sexes 52 , a pattern associated with bi-sexual dispersal in other primates 80 . Bi-sexual dispersal is supported in this subspecies, as over the course of the year, we observed a total of eight dispersals, four females and four males.…”
Section: Discussionmentioning
confidence: 56%
“…where groups typically average less than 20 individuals (reviewed by Fashing 51 ). Rwenzori Angolan colobus at our study site at Lake Nabugabo, Uganda form large groups of about 200 individuals and exhibit a greater degree of fission-fusion dynamics than reported at Nyungwe 52 . The aims of this study were 1) to determine if Rwenzori Angolan colobus at Nabugabo are forming a multi-level society and if so, 2) to determine the core unit composition and tier number.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We are just beginning to understand the social organization and social structure of C. angolensis ruwenzorii (Stead & Teichroeb, 2019) and the form of male relationships is still unclear. We know that within their unique multilevel society, adult males and adult females groom most frequently within core units (Arseneau‐Robar et al, 2018), which is supported by the bisexual dispersal we have observed from natal units (Stead & Teichroeb, 2019). However, the distance of dispersal between the sexes appears to differ.…”
Section: Discussionmentioning
confidence: 63%
“…; Rawson, 2009), proboscis monkeys ( Nasalis larvatus ; Yeager, 1990), snub‐nosed monkeys ( Rhinopithecus spp. ; Kirkpatrick & Grueter 2010; Qi et al, 2014), and recently Rwenzori colobus ( Colobus angolensis ruwenzorii ), which form temporary associations of more than 100 individuals at a lowland site in Uganda (Lake Nabugabo) (Arseneau‐Robar, Joyce, Stead, & Teichroeb, 2018; Stead & Teichroeb, 2019), are confirmed to have a multilevel society with three social tiers (Stead & Teichroeb, 2019). A study at the same site on proximity and grooming patterns reveals opposite‐sex bonding and weak same‐sex bonds within dyads of the Rwenzori colobus (Arseneau‐Robar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%